Composition and Significance of Bacterial Microbiota and Volatile Organic Compounds of Swiss-Dutch-Type Cheese as Determined by PCR-DGGE and HS-GC - Beata Nalepa; Magdalena Anna Olszewska; Lidia Hanna Markiewicz; Marek Aljewicz (Polish Journal of Food and Nutrition Sciences)
This study aimed to determine seasonal differences in the composition of bacterial microbiota and volatile organic compounds (VOCs) in Swiss-Dutch-type cheese (manufactured between 2012 and 2014). Bacterial diversity and VOCs (acetaldehyde; ketones: acetone, diacetyl, acetoin; alcohols: methanol, ethanol; esters: ethyl acetate, ethyl propionate, ethyl butyrate; fatty acids: acetic acid, propionic acid, isobutyric acid, butyric acid, isovaleric acid, valeric acid, isocaproic acid, caproic acid, heptanoic acid) were determined by polymerase chain reaction - denaturing gradient gel electrophoresis (PCR-DGGE), and headspace gas chromatography (HS-GC), respectively. Season influenced the composition of both bacterial microbiota and VOCs in cheese. Counts of starter bacteria ( Lactococcus, Leuconostoc and Propionibacterium – 6.51-7.14, 3.6-3.96 and 2.88-4.72 log CFU/g, respectively) were higher in the first year of the study, likewise these of the non-starter Lactobacillus (4.12-5.69 log CFU/g). The total VOC content was substantially lower in the summer-autumn 2012 (0.73228-3.34111 mg/g) than in the other seasons (63.28810-131.27690 mg/g). Differences in bacterial microbiota and the VOC profiles were observed between cheeses manufactured in winter-spring and summer-autumn seasons. Winter- and spring-manufactured cheeses were also characterized by a lower number of bacterial species (average 8.7-10.5 species/sample) than the cheeses produced in the summer and in the autumn (average 10-13 species/sample). The results of the study indicate that the cheese-making process has to be continuously monitored to minimize differences across manufacturing seasons.